2005
DOI: 10.1007/s00415-005-0940-7
|View full text |Cite
|
Sign up to set email alerts
|

Conservative treatments of children with episodic tension–type headache

Abstract: We found conflicting evidence about the effectiveness of relaxation therapy when compared with no treatment or other treatments, with Relative Risks varying from 1.4 (0.6-3.2) to 10.6 (1.6-71.3). With regard to all other interventions evaluated (such as biofeedback, cognitive therapy or flupirtin) no evidence is found for or against their effectiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…In total, there were 13 control groups (n = 133) that received a treatment designed to be consistent with the therapy in the active treatment groups, but without the specific active elements of the treatment. 9,11,12,14,16 This enabled the researchers to control also for attention, expectations of improvement, information, contact with the investigator, and medical equipment. There were many forms of pseudo-EMG biofeedback.…”
Section: Risk Of Biasmentioning
confidence: 98%
See 2 more Smart Citations
“…In total, there were 13 control groups (n = 133) that received a treatment designed to be consistent with the therapy in the active treatment groups, but without the specific active elements of the treatment. 9,11,12,14,16 This enabled the researchers to control also for attention, expectations of improvement, information, contact with the investigator, and medical equipment. There were many forms of pseudo-EMG biofeedback.…”
Section: Risk Of Biasmentioning
confidence: 98%
“…In total, there were 20 control groups including a WLC (n = 279). 11,12,14,16 Participants in these studies were placed on a waiting list. In most of the cases, they were told that the treatment groups were temporarily filled and the treatment would start within 2 to 12 weeks.…”
Section: Risk Of Biasmentioning
confidence: 99%
See 1 more Smart Citation
“…Global Health (1) scale$; (2) critical appraisal tool; (3) critical appraisal; (4) critical appraisal review; (5) appraisal of research methodology; (6) research design review; (7) quality assessment; (8) 1 or 2 or 3 or 4 or 5 or 6 or 7; (9) randomized controlled trial; (10) 8 and 9 80 HealthSTAR (1) scale$; (2) critical appraisal tool; (3) critical appraisal; (4) critical appraisal review; (5) appraisal of research methodology; (6) research design review; (7) quality assessment; (8) 1 or 2 or 3 or 4 or 5 or 6 or 7; (9) randomized controlled trial; (10) The included studies accounted for 21 scales and their modifications including: Jadad, 15,17,19,25,27,[60][61][62]64,[67][68][69]71,72,78,80,118,120,121,144 Maastricht, 3,62,126 Delphi List, 23,28,79,[81][82][83]90,92,99,[107][108][109][110] 13, 74,77,130,131,140,141 Maastricht-Amsterdam List (MAL), 29,85-90,93-97,99 -102,104 -106,112, 113,143 Van Tulder, 81, 82, 84, 91,92,98,103,107,108,110,111,114,142 Bizzini,26 Chalmers, 14,16,22,63,65,70,117,124,125,[127][128][129]138,139 Reisch,122,123 Andrew,115,116 Imperiale, 135 Detsky, 16,59 Cho and Bero, 119 Balas, 133 Sindhu, 20 Downs and Black,134 Nguyen, 137 Oxford Pain Validity Scale (OPVS), 21 Arrivé, 76 18,66,73,…”
mentioning
confidence: 99%
“…Relaxation therapy as a single therapy for children was reviewed with positive outcome by McGrath and Holahan (2004) although most studies involved children above 12 years of age or did not specify the exact age. Verhagen et al (2005) reviewed the effectiveness of conservative treatments in children with TTH with no evidence found for or against their effectiveness. Trautmann et al (2006) reported from a review significant headache reduction from relaxation therapy, biofeedback and cognitive behavioral therapy (CBT) though only a few reports included children and then only children with mixed headache or migraine headache.…”
Section: Relaxation Therapy and Biofeedbackmentioning
confidence: 99%